Journalist Competence in the Era of Artificial Intelligence Disruption - Sri Wahyuni; Rajab Ritonga; Reza Praditya Yudha (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
The rapid development of artificial intelligence (AI) has triggered a significant transformation in journalistic practice. This study aims to identify new competencies needed by journalists in facing AI disruption, analyse changes in the role of journalists due to the use of AI in the newsroom, and examine the forms of ethical and critical competencies needed in AI-based journalistic practices. This study uses the Systematic Literature Review (SLR) method on seven Scopus-indexed journal articles published between 2020 and 2025. The analysis results show that today's journalists must have technical competence in algorithms, critical skills in identifying bias and the social impact of AI, and ethical capacity that includes the principles of transparency, accountability, and justice. The role of journalists is no longer just as news producers, but as technology supervisors and guardians of public ethics in the era of content automation. This study emphasises the importance of establishing an adaptive and ethical competency framework to ensure that AI is used to strengthen journalistic integrity, not replace it.